A parentage study of closely related Ukrainian wine grape varieties using microsatellite markers - Goryslavets, S.; Risovanna, V.; Bacilieri, R.; Hausman, J.-F.; Heuertz, M. (Цитология и генетика, 2010)
Four bred grapevine varieties released for commercial cultivation in Ukraine, namely ‘Antey Magarachskii’, ‘Rubinovyi Magaracha’, ‘Granatovyi Magaracha’ and ‘Rubin Golodrigi’, and their putative parental forms were genotyped using six microsatellite loci.